Evaluasi Rasionalitas Penggunaan Antibiotik pada Neonatus dengan Infeksi Pneumonia Menggunakan Metode Gyssens di Rumah Sakit X Kota Bandung - Charisma Juni Kristianti; Duma Turu Allo; Donn Ricky (Indonesian Journal of Pharmaceutical Education, 2023)
Pneumonia is an inflammation of the lung tissue which is usually caused by a bacterial, viral or fungal infection. The disease can affect individuals of any age group, however, children, the elderly, and individuals with weakened immune systems are susceptible to potentially life-threatening pneumonia. Treatment therapy that is often carried out in overcoming the problem of pneumonia infection is by administering antibiotics. Inappropriate administration of antibiotics can cause less effective treatment, increase the risk of nosocomial infections, increase resistance, and side effects of drugs that are harmful to health. Rational use of antibiotics is important to avoid these negative consequences. The aim of this study was to determine the quality of antibiotic use in neonatal patients with pneumonia infections using the Gyssens method approach at Hospital Evaluation of antibiotic use was analyzed using Microsoft Excel. Retrospective design with data collection. Data analysis uses the Gyssens method flow diagram. The results showed that antibiotic use included Amikacin (15%), Amoxicillin (15%), Ampicillin (2%), Ampicillin Sulbactam (19%), Cefotaxime (19%), Ceftazidime (3%), Ceftriaxone (1%), Gentamicin(14%), Imipenem Cilastatin(1%), Meropenem(11%), Metronidazole(8%), Netilmicin(1%), Vancomycin(5%). Based on the research results, the conclusion of this study shows that the irrational use of antibiotics is a serious problem that requires immediate attention and joint action to protect the effectiveness of antibiotics and overall public health.